Effect of natural antioxidants on the physicochemical properties and stability of freeze‐dried microencapsulated chia seed oil. (15th October 2018) - Rodriguez, Erica S; Julio, Luciana M; Henning, Cynthia; Diehl, Bernd WK; Tomás, Mabel C; Ixtaina, Vanesa Y
Abstract: BACKGROUND: Chia oil possesses a very high content of polyunsaturated fatty acids, mainly α‐linolenic acid. This characteristic makes this oil possess beneficial properties to health but gives it a high susceptibility to the oxidation process. Microencapsulation and the addition of natural antioxidants are alternatives to protect chia oil against oxidative deterioration. The aim of this study was to investigate the physicochemical characteristics and the oxidative stability of chia seed oil microencapsulated with different natural antioxidants (Guardian Chelox, which is a commercial blend of extracts from chamomile and rosemary, and essential oils from Origanum vulgare, Origanum x majoricum, and Mentha spicata ) by freeze‐drying using sodium caseinate and lactose as wall materials. RESULTS: The main physicochemical properties of the microencapsulated chia oil were similar regardless of the presence of antioxidant. The moisture content was 38.1 ± 4.0 g kg −1 ; the microencapsulation efficiency was higher than 85% in all cases. The freeze‐drying microencapsulation significantly enhanced ( P ≤ 0.05) the oxidative stability of the chia oil. The addition of natural antioxidants conferred chia oil additional protection against lipid oxidation, depending on the type and concentration (500 or 1000 mg kg −1 of the emulsion previous to freeze‐drying) of the antioxidant. Among them, Guardian Chelox (1000 mg kg −1 ), presented the highest induction time obtained by the Rancimat accelerated oxidative stability test and the lowest peroxide values after 90 days of storage (33% relative humidity, 25 ± 2 °C). Overall, the microparticles with antioxidants presented a lower degree of yellowing during storage than the control system. CONCLUSION: The use of different natural antioxidants confers freeze‐dried microencapsulated chia seed oil additional protection against lipid oxidation. This information is relevant for the application of this oil, which is a rich source of omega‐3 fatty acids, in the food industry. © 2018 Society of Chemical Industry